Prescription drug coverage in Canada: a review of the economic, policy and political considerations for universal pharmacare - Jaden Brandt; Brenna Shearer; Steven G. Morgan (Taylor & Francis Group, 2018)
Background Canadians have long been proud of their universal health insurance system, which publicly funds the cost of physician visits and hospitalizations at the point of care. Prescription drugs however, have been subject to a patchwork of public and private coverage which is frequently inefficient and creates access barriers to necessary medicine for many Canadians. Methods A narrative review was undertaken to understand the important economic, policy and political considerations regarding implementation of universal prescription drug access in Canada (pan-Canadian pharmacare). PubMed, SCOPUS and google scholar were searched for relevant citations. Citation trails were followed for additional information sources. Published books, public reports, press releases, policy papers, government webpages and other forms of gray literature were collected from iterative internet searches to provide a complete view of the current state on this topic. Main findings Regarding health economics, all five of the reviewed pharmacare simulation models have shown reductions in annual prescription drug expenditure. However, differing policy and cost assumptions have resulted in a wide range of cost-saving estimates between models. In terms of policy, a single-payer, 'first-dollar' coverage model, using a minimum national formulary, is the model most frequently advocated by the academic community, healthcare professions and many public and patient groups. In contrast, a multi-payer, catastrophic 'last-dollar' coverage model, more similar to the current "patchwork" state of public and private coverage, is preferred by industry drug manufacturers and private health insurance companies. Primary concerns from the detractors of universal, single-payer, 'first-dollar' coverage are the financing required for its implementation and the access barriers that may be created for certain patient populations that are not majorly present in the current public-private payer mix. Conclusion Canada patiently awaits to see how the issue of prescription drug coverage will be resolved through the work of the Advisory Council on the Implementation of National Pharmacare. The overarching and ongoing discourse on policy and program implementation may be construed as a political debate informed by divergent public and private interests.